المقاصد الضرورية من خلال سورة الممتحنة - عبدالله، عطية غالب (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
هذا بحث يتناول البيان للمقاصد الضرورية من خلال سورة الممتحنة، مسبوقة ببيان معنى المقاصد الشرعية، وبيان معنى الضرورية، واشتمل على التعريف بسورة الممتحنة، وأسباب نزولها، وما يتعلق بها. المنهج المتبع: الاستنباطي الاستقرائي أهمية البحث: تظهر أهميته في بيان المقاصد الضرورية الشرعية في تلك السورة؛ من أجل فهمها على ما ينبغي وفق مقاصدها ومن أهم نتائج البحث ما يلي: 1. المقاصد الشرعية هي: إرادة الشارع في تشريعه للأحكام بما يحقق العبودية لله تعالى وتحقيق المصالح للعباد في الدارين. 2. إن علم المقاصد هو السبيل لفهم المراد من كلام الله تعالى السور، والغايات التي أنزلت من أجله وعلاقتها بالواقع. 3. إن لكل سورة مقاصد، ومناسبات، وغايات فلم تأت السورة بما حوت من الآيات جزافاً، وسورة الممتحنة واحدة من السور التي حوت معاني ومقاصد عظيمة لها الأثر في عقيدة المسلم. 4. مقصد السورة الأول هو حفظ الدين وذلك بالتبرأ من المشركين، وعدم موالاتهم، والبراءة منهم ومن أفعالهم، وسؤال الله الثبات على الإيمان، واتخاذ الوسائل المعينة على ذلك، من اتخاذ الأسوة الصالحة الحسنة وغيرها. 5. بناء القرآن على مقاصد عامة ترجع إليها جميع معاني سوره وآياته. This research deals with the statement of the necessary purposes through Surat Al-Mumtahanah, preceded by a statement of the meaning of the legitimate purposes, and a statement of the meaning of the necessary, and included the definition of Surat Al-Mumtahanah, the reasons for its revelation, and what is related to it. Methodology: Inductive Deductive The importance of research: Its importance appears in the statement of the necessary purposes of legitimacy in that surah, in order to understand them properly according to their purposes. Among the most important findings of the research are the following: 1. The legitimate purposes are: the will of the street in its legislation of rulings in order to achieve slavery to God Almighty and achieve the interests of the servants in the two worlds. 2. The science of purposes is the way to understand what is meant by the words of God Almighty, the surahs, the goals that were revealed for him and their relationship to reality. 3. Each surah has purposes, occasions, and goals, so the surah did not come with the verses arbitrarily, and Surat Al-Mumtahanah is one of the surahs that contained great meanings and purposes that have an impact on the belief of the Muslim. 4. The first purpose of the surah is to preserve religion by repudiating the polytheists, disowning them, disowning them and their actions, asking God to remain steadfast in faith, and to take the means to help that, from taking the good and good example and others. 5. Building the Qur’an on general purposes to which all the meanings of its surahs and verses are referenced.
Keywords: القرآن الكريم -- تفسير القرآن -- المقاصد الشرعية -- السور والآيات